Integrating Logotherapy and Islamic Guidance in Career Counseling: Addressing Quarter Life Crisis Among Muslim Young Adults - Nina Siti Marlina (P3M STAI Kuningan, 2024)
Background: Quarter-life crisis among Muslim young adults represents a complex developmental challenge characterized by career uncertainty, identity confusion, and existential anxiety. Conventional secular career counseling inadequately addresses this phenomenon due to its neglect of spiritual dimensions that are central to Islamic identity and meaning-making processes.Objective: This study aimed to develop and examine an integrative career counseling framework that combines logotherapy's meaning-centered principles with Islamic spiritual guidance to address quarter-life crisis among Muslim young adults.Method: Employing interpretative phenomenological analysis, this investigation examined twenty-two Muslim young adults aged 22–32 years who completed 6–8 individual counseling sessions. Data were collected through recorded sessions, reflective journals, and post-intervention interviews, generating 1,847 pages of transcripts analyzed using NVivo software.Findings and Implications: The phenomenological analysis revealed five superordinate themes: existential awakening through spiritual reconnection, liberation from materialistic success paradigms, meaning-centered career reconstruction, integration of professional and spiritual identities, and empowerment through existential choice. These themes demonstrate that spiritual reconnection serves as a foundational catalyst, enabling comprehensive career clarity and identity coherence.Conclusion: This research demonstrates that effective career counseling for Muslim young adults necessitates the explicit integration of meaning-centered psychological approaches with Islamic spiritual guidance, providing validated protocols for culturally responsive counseling practice and theoretical foundations for future research examining spiritually integrated interventions across diverse religious populations.